Republic of Madagascar : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Activation of the Trade Integration Mechanism-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2006)
Madagascar is one of the poorest countries in sub-Saharan Africa, ranking 146 out of 177 on the United Nations Human Development Index. The country has one of the lowest tax revenue-to-GDP ratios in the world (10.1 percent in 2005). To address these challenges, the authorities are requesting a new three-year arrangement under the Poverty Reduction and Growth Facility (PRGF) to support their economic program for 2006-08. Broad money growth declined sharply in 2005, but credit to the private sector was strong. The banking system is profitable and well capitalized.